A REVIEW OF CONSTRAINT FACTORS IN COMPLYING WITH BUILDING CONTROL REGULATION RELATED TO HOUSE RENOVATION - Kamarulzaman, Putri Nabila; Azmi, Nur Farhana; Sulaiman, Raha (Journal of Surveying, Construction and Property, 2019)
The purpose of the study is to provide a review on the constraint factors in complying with building control regulation related to house renovation. Adapting the qualitative approach, an extensive review was made on the existing literature related to the constraint factors to comply with building control regulation and guidelines with regards to house renovation. The study found that the constraint factors can be classified into four main categories based on the perspective of four key stakeholders’ groups in renovation works; law and policy maker, local authority, the professionals, and homeowners. The complexity of existing building legislation and guideline has been identified as the most fundamental issue that contributes to non-compliant renovation works in Malaysia. The paper concludes with the recommendation that the current legislations and guidelines pertaining to house renovation in the country need to be reviewed considering the interest of stakeholders. This study is deemed to be one of many researches that contribute to the existing gap in literature on building control with regards to existing buildings.